2000
DOI: 10.1108/02641610010694956
|View full text |Cite
|
Sign up to set email alerts
|

Interlending and document supply: a review of recent literature – XXXVII

Abstract: Reviews literature related to several aspects of interlending and document supply. Examines the impact of World Wide Web delivery and the ever‐increasing number of periodicals being published electronically. Interlinked with these two factors is the creation of digital libraries. Discusses some of the projects undertaken by higher education institutions to deliver electronic material to researchers and students. Includes articles on various resource sharing activities highlighting the usual access versus owner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Literature reviews published by Connolly (2000Connolly ( , 2001, Gould (2000Gould ( , 2001Gould ( , 2002 and McGrath (2002McGrath ( -2007, in the journal Interlending and Document Supply, highlight continued interest both in the access versus ownership debate and in resource sharing. These reviews also highlight a growing body of literature on automation, unmediated document delivery, copyright, electronic resources, consortia, as well as licensing and pricing as it relates to the so-called 'big deals" In recent years, many articles have been published on the subjects of open access, e-books, digitization and Google.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature reviews published by Connolly (2000Connolly ( , 2001, Gould (2000Gould ( , 2001Gould ( , 2002 and McGrath (2002McGrath ( -2007, in the journal Interlending and Document Supply, highlight continued interest both in the access versus ownership debate and in resource sharing. These reviews also highlight a growing body of literature on automation, unmediated document delivery, copyright, electronic resources, consortia, as well as licensing and pricing as it relates to the so-called 'big deals" In recent years, many articles have been published on the subjects of open access, e-books, digitization and Google.…”
Section: Literature Reviewmentioning
confidence: 99%
“…. A review of recent literature on interlending and document supply, (Connolly, 2000), cites only one source related to CEE and Nordic-Baltic countries.…”
Section: Intellectual Property Protectionmentioning
confidence: 99%
“…But optimistically, the important first step – a legal framework, has been introduced in almost all CEE countries. Even in the field of library and information science, publication is difficult and clearly shown by the following examples:A review of recent literature on interlending and document supply, (Connolly, 2000), cites only one source related to CEE and Nordic‐Baltic countries.Uzun (2002) examined a set of 21 core journals in the field of library and information science (LIS) from 1980‐1999 for articles with either principal or co‐authors from developing countries (DCs) and the formerly socialist CEE countries. “We found that only 826 (7.9 per cent) of a total of 10,400 articles published in 21 journals are from DCs or CEEs” (Uzun, 2002).…”
Section: Intellectual Property Protectionmentioning
confidence: 99%
“…DELNET is a resource-sharing library network in India (Kaul, 2010); (McGrath, 2009); (Connolly, 2000). DELNET is a non-governmental, non-profit organisation and is located at Jawaharlal Nehru University, New Delhi, India.…”
Section: Introductionmentioning
confidence: 99%